The Burden of Influenza in Children - Libster, Romina; Edwards, Kathryn M. (Pediatric annals, 2010)
The threat of an influenza pandemic and the desire to generate more immunogenic influenza vaccines has stimulated the evaluation of a number of new vaccine adjuvants. The increased use of either inactivated or live influenza vaccines directed at seasonal and pandemic strains has the potential to reduce the influenza disease burden in children and to potentially extend herd protection to those who are unvaccinated.